Governança universitária : proposta para criação de um observatório na Universidade Federal de Sergipe - Albuquerque, Kátia Ferreira de (2022)
Public administration is constantly seeking to evolve, seeking to improve its mechanisms to better meet society's needs and provide more and more quality services. In the same vein are the Brazilian Federal Universities, members of the federal public administration, implementing management strategies that seek to achieve better results. In this scenario, the federal government published Decree No. 9.203/2017, which determines the governance policy, which must be adopted by the direct, autonomous and foundational federal public administration, including the federal universities, in order to bring a minimum consensus about what governance is and the principles that should guide good governance practices. This research aims to outline guidelines for a governance tool at the Federal University of Sergipe - UFS, which strengthens and deepens the governance mechanisms implemented in this institution, in order to support management in decision-making. In this sense, we seek to outline the contours of a governance observatory for the UFS, which provides ample interaction between sectors, generating reliable information and data to make the decision-making process safer, more efficient and effective. For this purpose, we used the guidelines on governance established by the Federal Court of Accounts - TCU and a vast theoretical framework, establishing, from there, what are the governance pillars within a public university, what are the essential elements for the construction of a governance observatory and how this observatory can help management in decisionmaking, to then present a project for the creation of a governance observatory at UFS. In methodological terms, this research has a qualitative approach, identifying the governance practices adopted by the institution, the structures for the governance observatory and the contributions that its activities will provide. As for the objectives, it is classified as descriptive, because from the technical procedures of bibliographic and documentary research, the characteristics of governance at UFS and observatories were identified, interpreting the collected data that culminated in the presentation of the structures for the implementation of an observatory of governance at the Federal University of Sergipe.